2020
DOI: 10.1111/mpp.12924
|View full text |Cite
|
Sign up to set email alerts
|

Green leaf volatiles and jasmonic acid enhance susceptibility to anthracnose diseases caused by Colletotrichum graminicola in maize

Abstract: Colletotrichum graminicola is a hemibiotrophic fungus that causes anthracnose leaf blight (ALB) and anthracnose stalk rot (ASR) in maize. Despite substantial economic losses caused by these diseases, the defence mechanisms against this pathogen remain poorly understood. Several hormones are suggested to aid in defence against C. graminicola, such as jasmonic acid (JA) and salicylic acid (SA), but supporting genetic evidence was not reported. Green leaf volatiles (GLVs) are a group of well-characterized volatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 78 publications
7
49
1
Order By: Relevance
“…ZmLOX10 provides substrate to several LOX branches and produces a series of 13-oxylipin products, and the zmlox10 plants were unable to produce green leaf volatiles (GLVs) and JA, resulting in a dramatic decline in herbivore-induced plant volatiles and attractiveness to parasitoid wasps [51,52]. A recent study has revealed that GLVs and JA contribute to maize susceptibility to Colletotrichum graminicola due to the suppression of SA-related defense [53]. Hence, the ClLOX genes may participate in the protection of plants from biotic stresses by catalyzing the synthesis of some oxylipins through the regulation of the SA-and ET/JA-mediated defense response pathways.…”
Section: Discussionmentioning
confidence: 99%
“…ZmLOX10 provides substrate to several LOX branches and produces a series of 13-oxylipin products, and the zmlox10 plants were unable to produce green leaf volatiles (GLVs) and JA, resulting in a dramatic decline in herbivore-induced plant volatiles and attractiveness to parasitoid wasps [51,52]. A recent study has revealed that GLVs and JA contribute to maize susceptibility to Colletotrichum graminicola due to the suppression of SA-related defense [53]. Hence, the ClLOX genes may participate in the protection of plants from biotic stresses by catalyzing the synthesis of some oxylipins through the regulation of the SA-and ET/JA-mediated defense response pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike SA, JA and its derivatives, methyl jasmonate (MeJA) and jasmonoyl isoleucine (JA-Ile), function as signaling molecules in plant defense against necrotrophic pathogens and chewing insects [ 24 , 63 , 64 ]. JA is synthesized in vascular bundles, which also host prosystemin biosynthesis, and JA, systemin and prosystemin are related to each other in a double feedback manner [ 65 , 66 ].…”
Section: Building Blocks and Molecular Mechanisms Of The Plant Snsmentioning
confidence: 99%
“…Multiple roles of JA in maize are best illustrated in the study of the opr7opr8 double mutant, which is deficient in JA biosynthesis, is male-sterile, lacks anthocyanin production, and is susceptible to soil-borne pathogen Pythium spp. [ 18 ] and Fusarium verticillioides [ 20 ], but resistant to anthracnose leaf blight and stalk rot, caused by a hemibiotrophic pathogen Colletotrichum graminicola [ 21 ]. Although underappreciated previously, 12-OPDA has been increasingly drawing attention as having functions distinct from those of JAs [ 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, a recent study revealed that 12-OPDA and α-ketol of octadecadienoic acid (KODA), but not JA, serve as the mobile signals in Trichodema -elicited induced systemic resistance (ISR) [ 28 ]. Moreover, while exogenous treatment of maize with MeJA results in increased susceptibility to C. graminicola [ 21 ], application of 12-OPDA results in increased resistance to this pathogen [ 27 ].…”
Section: Introductionmentioning
confidence: 99%